Extending the FSM Model for Critical Decision-Making and Safety Control in Autonomous Vehicles - Selvi , V. Tamil; Dhurgadevi , M.; Prithiviraj, Prithiviraj; Jackulin, T.; Baskaran, K. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Safety and security are important when it comes to the generation of autonomous vehicles. Therefore when there is any drawback in the normal autonomous vehicle then it will not gain a good reach among the audience. The main aim of this autonomous vehicle is to give good transport service without human intervention. The decision-making and control of vehicle speed and direction and the necessary features are required to be improved to avoid damage or problem to the pedestrians and also to the car. Thus to improve the enhanced autonomous vehicle transportation that is good in the decision making and controlling the car driving is possible using this proposed FSM model in this research paper. This finite state machine model will give satisfaction and easy control of the autonomous vehicle which means that it will give a good travelling experience to the customers. Good detection of the pedestrian using the sensors and moving the car with maneuver is possible with this model. Once this is implemented the autonomous vehicles that contain this FSM technique will surely clear all the traffic problems and obstacles like center medians, potholes, zebra crossing, traffic signals, etc. that are present in any kind of road conditions or traffic. Driving the car with maneuvering is now possible using autonomous intelligence and the proposed and trending FSM model. Final evaluations on the recommended technique’s effectiveness and engineering practicality comprise simulation studies and outdoor operating trials. Control of autonomous vehicles in tough road conditions will be enhanced when compared to human driving. Furthermore, the entire structure is very scalable for unsupervised vehicle driving under various traffic environments.